2022
DOI: 10.1192/j.eurpsy.2022.22
|View full text |Cite
|
Sign up to set email alerts
|

The early impact of the COVID-19 pandemic on patients with severe mental illness: An interrupted time-series study in South-East England

Abstract: Background Deterioration in general population mental health since the start of the COVID-19 pandemic has been reported, but the impact of the pandemic on people with severe mental illness (SMI) has received less attention. Aims To understand the impact of the early stages of the pandemic on the patients with SMI, in terms of provision of mental health care and patient outcomes. Method We examined records of 34,446 patients with SMI in Oxford Health Foundation Trust bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
1
7
1
2
Order By: Relevance
“…One study in South Africa found that the levels of hospital admissions and outpatient consultations were reduced from the COVID-19 blocking measures, and during the pandemic there was a gradual recovery process in the number of hospital admissions (Wettstein et al, 2022). In other study performed in South-East England, the trend was similar to the previous study, outpatient and community care in mental health services decreased since the application of COVID-19 confinement, followed by a gradual recovery of care (Penington et al, 2022).…”
Section: Discussionsupporting
confidence: 82%
“…One study in South Africa found that the levels of hospital admissions and outpatient consultations were reduced from the COVID-19 blocking measures, and during the pandemic there was a gradual recovery process in the number of hospital admissions (Wettstein et al, 2022). In other study performed in South-East England, the trend was similar to the previous study, outpatient and community care in mental health services decreased since the application of COVID-19 confinement, followed by a gradual recovery of care (Penington et al, 2022).…”
Section: Discussionsupporting
confidence: 82%
“…However, due to the spread of epidemics and pandemics in the past years, infectious diseases have also been addressed as one of the vulnerabilities in these patients [ 9 ]. Six large-scale studies from Sweden ( N = 195,565), Denmark ( N = 144,321), Israel ( N = 125,273), the UK ( N = 447,296), England ( N = 34,446), and the US ( N = 7,348) showed an increased risk of the COVID-19 infection, hospitalization, and mortality for patients with SPDs, with no increased risk for other psychiatric disorders such as anxiety disorders [ 3 , 9 , 11 14 ]. A South Korean cohort study found that patients with SPDs had a slightly higher risk for severe clinical outcomes of COVID-19 than patients without psychiatric disorders [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Darüber hinaus sind psychosoziale Stressoren während der Pandemie bislang nicht systematisiert worden. Psychosoziale Vulnerabilität und Stressoren zu definieren, zu systematisieren und zu operationalisieren wären wichtige Voraussetzungen, um neben den Risiken direkter Gesundheitsfolgen durch COVID- 19…”
Section: Introductionunclassified
“…Hierbei hatten diese im Mittel im Vergleich zu gesunden Kontrollstichproben während der Pandemie deutlich erhöhte Angst-, Depressions-und Stresswerte.Dabei fiel jedoch die Belastung für Menschen mit schweren depressiven Erkrankungen gravierender aus als für Personen mit einer Schizophrenie. Zudem wurde aufgezeigt, dass ein jüngeres Alter mit gravierenderen Symptomen assoziiert war[19]. Eine neuere, Zeitreihen-basierte Studie wertete Routinedaten des Oxford Health Foundation Trusts von insgesamt 34.446 Patient*innen mit SMI aus.…”
unclassified